Approach to Informed Consent in Telepsychiatric Service: Indian Perspective. Issue 5 (October 2020) - Gowda, Guru S; Enara, Arun; Ali, Furkhan; Gowda, Mahesh R; Basavarajappa, Chethan; Kumar, Channaveerachari Naveen; Math, Suresh Bada
Consent is an essential and important medico-legal prerequisite for a patient's treatment. This necessitates the service provider to participate in the informed consent process and discuss the risk-benefit of the proposed treatment, the best available treatment, engage in shared decision-making process, opportunity to convey their view and thereby limit chances of legal liability for all parties. The clinician should have ample knowledge and skill pertaining to the informed consent process and also have adequate understanding of medical ethics and law. This article provides an overview on informed consent pertaining to telepsychiatric services in India.